ANTIBACTERIAL ACTIVITY OF BELILIK (Brucea javanica (L). MERR) AND BENTA (Wikstroemia androsaemofolia DECNE) TO INHIBIT THE GROWTH OF ENTEROPATHOGENIC BACTERIA - Henny Helmi; Idha Susanti; Noptian Asmara Agung; Sadam Kusen (The East Java Biological Society, 2015)
Several native Indonesia plants have been used to prepare traditional medicine since long time ago. One of common diseases in tropical country is diarrhea, it caused by the infection of enteropathogenic bacteria such as Enteropathogenic Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Shigella sp. Belilik (Brucea javanica (L.) Merr) and Benta (Wikstroemia androsaemofolia Decne) are herbals that utilized as medicine for diarrhea in Bangka Belitung, Indonesia. Parts of these plants are mostly can be utilized as medicine, such as leaf, root, and fruit. The aims of this study were to investigate the antibacterial activity of ethanol crude extract of B. javanica (root and fruit) and W. androsaemofolia (leaf and fruit) against enteropathogenic bacteria (EPEC, P. aeruginoa, S. aureus, Shigella sp.). Meth od that used was papper disc diffusion. The results showed that at concentration 10 mg/mL, 20 mg/mL, and 30 mg/mL of B. javanica ethanol extract of both root and fruit could not inhibit the enteropathogenic bacteria, while the ethanol extract of leaf and fruit of W. androsaemofolia were shown inhibition activity on the growth of enteropathogenic bacte ria. W. androsaemofolia leaf extract performed the best inhibition activity to the growth of EPEC (20.55±1.5mm) and S. aureus (22.14±4.5mm), it was better than kanamycin performance at the same concentration (30 mg/mL). In addition, ethanol extract of W. androsaemofolia fruit showed the best inhibition activity against Shigella sp. (19.64±1.8mm).